Seyyed Hossein Nasr's Teaching on Sufism and Its Relevance to Modern Society - Amir Maliki Abitolkha (Jurnal Theologia, 2021)
This article examines Seyyed Hossein Nasr's teaching on Sufism and its relevance to modern society. The fact is that the paradigm and lifestyle of modern humans are materialism-oriented. Therefore, they experience a spiritual emptiness that causes anxiety. This study applies the literature approach by collecting various related sources. This study found that Seyyed Hossein Nasr's idea of neo-Sufism can be an alternative paradigm for modern people to free themselves from the threat of materialism and hedonism. The Divine spirit of humans will form spiritual power in the human soul to keep the connectivity between the servant and God. Nasr's teaching on Sufism puts forward the concept of balance and moderation between the life in this world and hereafter, between shari'ah and haqeqat, and between individual and social life.